Cellular Agriculture for Production of Cell-Based Seafood - Razieh Farzad (EDIS)
This new 4-page article intends to give basic information about the cell-based seafood production system to consumers and seafood producers. Written by Razieh Farzad and published by the UF/IFAS Food Science and Human Nutrition Department.